Respuesta :
Let a and b be the factors of the expression such that x² + 9x + 20 = (x + a)(x + b). The sum of a and b is the numerical coefficient of the second term and their product is the constant.
a + b = 9 ; a = 9 - b
ab = 20 ; (9 - b)(b) = 20
The value of a and b are 4 and 5. The factors are therefore,
(x + 4)(x + 5)
To find the zero, equate the factors to zero which yields an answer equal to x = -4 and x = -5.
a + b = 9 ; a = 9 - b
ab = 20 ; (9 - b)(b) = 20
The value of a and b are 4 and 5. The factors are therefore,
(x + 4)(x + 5)
To find the zero, equate the factors to zero which yields an answer equal to x = -4 and x = -5.
The zero's of the functions are x =-4 and x = -5
Zero's of quadratic equation:
The zeros of a quadratic equation are the points where the graph of the quadratic equation crosses the x-axis.
we equate the given quadratic function to 0 and solve for the values of x that satisfy the quadratic equation.
Therefore, the zero's by factoring is as follows;
- f(x) = x² + 9x + 20
f(x) = x² + 9x + 20
f(x) = x² + 5x + 4x + 20
0 = (x+4)(x+5)
Therefore, the zeros are as follows:
- x + 4 = 0; x = -4
- x + 5 = 0; x = -5
learn more on function here: https://brainly.com/question/14400360